Habitual dietary lactose and galactose intakes in association with age at menopause in non-galactosemic women. - Marzieh Rostami Dovom; Nazanin Moslehi; Parvin Mirmiran; Fereidoun Azizi; Fahimeh Ramezani Tehrani (PLoS ONE, 2019)
Introduction Rodent models and studies on women with galactosemia suggest the ovo-toxicity effect of galactose. However, the association between galactose intake from dietary sources and the ovarian function in women without galactosemia has not yet been described. Therefore, this study aimed to investigate the associations between both dietary galactose and lactose intake, and ovarian dysfunction as the odds of early menopause in women without galactosemia. Materials and methods This cross-sectional study was conducted on 821 women without galactosemia, participants of the Tehran Lipid and Glucose Study (TLGS), who experienced natural menopause. Habitual dietary intakes of lactose and galactose during the past 12 month were assessed, using a food-frequency questionnaire (FFQ). In this study, early menopause was defined as natural menopause before the age of 45 years. Results Mean- and menopausal age of women were reported as 59.3±7.94 and 48.6±4.81 years, respectively. No statistically significant linear association was observed between the daily intakes of lactose and galactose and the odds of early menopause. After adjusting for age, energy intake, and age at menarche, women in the middle tertiles of lactose (62%, 95%CI: 1.07, 2.46) and galactose (58%, 95% CI: 1.05, 2.39) intake had significantly higher odds of early menopause, than those in the first tertile. When the daily intake of lactose and galactose were expressed as the percentage of energy intake, the higher odds of early menopause among women in the middle tertile compared to those with the first tertile were reduced and became non-significant. Conclusion No statistically significant linear associations were reported between the intake of lactose and galactose and age of menopause. However, the odds of early menopause in those women with the middle tertile of lactose and galactose intake were significantly higher than those women in the first tertile.